Path Analysis Model in Determining the Crime Rate During the Covid 19 Pandemic in North Sumatera - Wardani, Yuni; Darnius, Open (Journal of Mathematics Technology and Education, 2022)
Path analysis is a research method that is mainly used to examine the strength of direct and indirect relationships among various variables. This is in line with one of the objectives of research in social science, namely to determine the existence of a causal relationship. Path analysis can be applied to a social issue, currently the world is worried about the spread of COVID-19. The existence of policies in controlling the spread of COVID-19 disrupts various aspects of life. This study was conducted to determine the factors that cause crime in North Sumatra and to determine the effect of the COVID-19 on the rise of crime rates using the path analysis method. In this study, it was concluded that although there are several exogenous variables that have decreased influence on endogenous variables in 2020, but in this year, which is the pandemic period, the coefficient of determination has the best level.